A genome-wide study of panic disorder suggests the amiloride-sensitive cation channel 1 as a candidate gene - Gregersen, Noomi (Nature Publishing Group, 2012)
Panic disorder (PD) is a mental disorder with recurrent panic attacks that occur spontaneously and are not associated to any particular object or situation. There is no consensus on what causes PD. However, it is recognized that PD is influenced by environmental factors, as well as genetic factors. Despite a significant hereditary component, genetic studies have only been modestly successful in identifying genes of importance for the development of PD. In this study, we conducted a genome-wide scan using microsatellite markers and PD patients and control individuals from the isolated population of the Faroe Islands. Subsequently, we conducted a fine mapping, which revealed the amiloride-sensitive cation channel 1 (ACCN1) located on chromosome 17q11.2-q12 as a potential candidate gene for PD. The further analyses of the ACCN1 gene using single-nucleotide polymorphisms (SNPs) revealed significant association with PD in an extended Faroese case–control sample. However, analyses of a larger independent Danish case–control sample yielded no substantial significant association. This suggests that the possible risk alleles associated in the isolated population are not those involved in the development of PD in a larger outbred population.